Analisis hadith mengenai zikir dalam al-Kutub al-Sittah: Pengamalan dalam majlis zikir tarekat tasawuf di Negeri Sembilan / Mohammad Fahmi Abdul Hamid - Mohammad Fahmi , Abdul Hamid (2019)
This study focuses on the practice of zikir in tasawuf tariqa zikir ceremony. Problems arose when allegations were made that the practice of zikir was against the al-Sunnah discourse. Therefore, this research identifies the Prophet (PBUH) method of zikir according to zikir-related hadiths in the al-Kutub al-Sittah where every element of the zikir practice are in tandem with the ruling stated in al-Sunnah through further discourse. An institution of tasawuf tariqa in Negeri Sembilan was the focus of this study based on its capacity being the only state that has a state level Tasawuf Tariqa Enactment. This study applied the qualitative methodology, which is a descriptive analysis of nature. Observation and interviews approaches were employed to monitor the zikir process in the zikir ceremony as practised by the tasawuf tariqa practitioners in Negeri Sembilan. The analysis mechanism for the field data used hadiths as its main evidence (dalil), supported by proof from the al-Qur’an as well as fatwas issued by Muslim scholars (ulama) to discern that the zikir practice concurs with the al-Sunnah discourse. Meanwhile, data of the interview with the tariqa sheikh in Negeri Sembilan are deemed supporting data that enhanced the findings in hand. The findings showed that there are 298 zikir-related hadiths in the al-Kutub al-Sittah, which comprised 237 ṣaḥīḥ, 32 ḍa‘īf, 18 ḥasan, four ḥasan ṣaḥīḥ, four munkar, two ḍa‘īf jiddan and one mawḍū‘. Nine main focus of the hadiths were identified, namely suggestion, type, method, the rate of voice, time, number, pronouncement, location, and the reward of zikir. Religious scholars contradict in four of those components, namely method, number, pronouncement, and rate of voice during zikir. A polemic at the field level showed that two components were against the al-Sunnah and were wholly rejected—using excessive rate of voice and overdoing to the point of shouting as well as zikir accompanied by rhythm and music. Finally, the findings presented a “preliminary framework of zikir practice in tasawuf tariqa zikir ceremony” as a beneficial added value to policymakers, tariqa practitioners, and the society in solidifying the tasawuf tariqa institute in Negeri Sembilan. This guideline could also coordinate all activities or the practice of zikir in tasawuf tariqa zikir ceremony, thus, eradicating any issue that could jeopardize the practice of tasawuf tariqa zikir.